Methods for Evaluation of Webometric Indicators of Public Library - Diyora Talipova,; Gaziyev Asqar,; Ziyodullayeva Gulchiroy, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
The purpose of this research is to develop the method for analysing public library websites in order to improve their monitoring efficiency and provide fast and high-quality remote services to users. In this article, the authors provide a general understanding of the analysis of webometric indicators of library websites and their evaluation methods. Indicators for each criterion and sub-criterion are provided to help determine the importance of library websites. Information is provided on the evaluation of all criteria by experts and their calculation using complex mathematical methods. As part of the research, an analytical conclusion was made based on 14 library websites were evaluated by experts. Through this research, it is important to determine the popularity of public library websites, compare them and improve the efficiency of the library.
Keywords: Method; Public Library; Assessment; Webometrics; Website; Value; Expert Evaluation